Fluidized bed two-stage O2/steam gasification of agricultural biomass for low-tar syngas: An industrial-scale verification test - Chao Wang; Gang Song; Mengjuan Zhang; Kaixuan Yang; Zhenglin Wang; Xin Jia; Qingya Liu; Liguo Zhou; Zhennan Han; Shurong Wang; Jianguo Bian; Guangwen Xu (Carbon Resources Conversion, 2025)
In the complete green synthesis technology chain, bio-syngas production remains the “first hurdle”. Especially, the “tar” problem in biomass gasification urgently needs to be solved. Recently, our team, in collaboration with Jinan Huangtai Gas Stove Co., Ltd., completed a 10,000-ton industrial test and technical verification of fluidized bed two-stage O2/steam gasification for production of syngas from biomass. The test results showed that the fluidized bed two-stage gasification was operated continuously and stably for over 110 h with various biomass feedstocks. Additionally, the lowest tar content in the produced gas reached 0.58 g/Nm3. The fly ash collected from the continuous test contained carbon of about 30 wt%. Thus, the technology was well proved for large-scale biomass gasification and production of syngas in terms of technical feasibility and operational stability.